2015
DOI: 10.1111/mmi.12978
|View full text |Cite
|
Sign up to set email alerts
|

The targeted recognition of Lactococcus lactis phages to their polysaccharide receptors

Abstract: SummaryEach phage infects a limited number of bacterial strains through highly specific interactions of the receptor-binding protein (RBP) at the tip of phage tail and the receptor at the bacterial surface. Lactococcus lactis is covered with a thin polysaccharide pellicle (hexasaccharide repeating units), which is used by a subgroup of phages as a receptor. Using L. lactis and phage 1358 as a model, we investigated the interaction between the phage RBP and the pellicle hexasaccharide of the host strain. A core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“… Comparison of the four RBPs from lactococcal phages of known structure. (A to D) RBPs of phages 1358 ( 40 , 77 ) (A), p2 ( 53 ) (B), TP901-1 ( 25 , 42 ) (C), and Tuc2009 (D). The RBP trimers are rainbow colored.…”
Section: Discussionmentioning
confidence: 99%
“… Comparison of the four RBPs from lactococcal phages of known structure. (A to D) RBPs of phages 1358 ( 40 , 77 ) (A), p2 ( 53 ) (B), TP901-1 ( 25 , 42 ) (C), and Tuc2009 (D). The RBP trimers are rainbow colored.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, ϕ11 Gp45, the RBP, does not exhibit analogy with other phage RBPs, in particular with those from lactococcal phages that also bind to saccharidic receptors. Lactococcal phages p2 52, TP901-1 53, Tuc2009 19, bIL170 54 and 1358 4 all possess a trimeric receptor recognition head sharing a bona fide or a modified jelly-roll motif. The rest of their RBPs share common motifs in the neck or in the N-terminal domain (or stem).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies failed to reveal a significant phage resistant phenotype in EPS and CPS producer strains ( Deveau et al, 2002 ; Rodriguez et al, 2008 ); in contrast, McCabe et al (2015) recently reported on the targeted recognition of Lactococcus lactis phages to their polysaccharide receptors.…”
Section: Role Of Eps-producing Lab and Their Polymersmentioning
confidence: 98%